2021
DOI: 10.1007/s00203-021-02300-y
|View full text |Cite
|
Sign up to set email alerts
|

Presence of non-oral bacteria in the oral cavity

Abstract: A homeostatic balance exists between the resident microbiota in the oral cavity and the host. Perturbations of the oral microbiota under particular conditions can contribute to the growth of non-oral pathogens that are hard to kill because of their higher resistance to antimicrobials, raising the probability of treatment failure and reinfection. The presence of these bacteria in the oral cavity has been proven to be associated with several oral diseases such as periodontitis, caries, and gingivitis, and system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 115 publications
1
27
0
Order By: Relevance
“…Nevertheless, there is a controversy about whether non-oral bacteria are merely transient or unique to this niche but in recent times substantial evidence in different studies has highlighted the role of these bacteria in dental disease either with coordinated co-operative behaviors in the presence of normal oral microbiota [1,6,25,30,31,32]. Additionally, some of these non-oral bacteria isolates from the oral cavity of patients with dental disease in this study, have been reported to be genetically different from strains from other parts of the human body [33], which could potentially lead to another understanding of the ecosystem of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, there is a controversy about whether non-oral bacteria are merely transient or unique to this niche but in recent times substantial evidence in different studies has highlighted the role of these bacteria in dental disease either with coordinated co-operative behaviors in the presence of normal oral microbiota [1,6,25,30,31,32]. Additionally, some of these non-oral bacteria isolates from the oral cavity of patients with dental disease in this study, have been reported to be genetically different from strains from other parts of the human body [33], which could potentially lead to another understanding of the ecosystem of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…However, failure to remove plaque by regular toothbrushing allows them to proliferate, unchecked, and thereby build up in a thick layer, which can by their ordinary metabolism cause various dental diseases to the host [42]. The ability of S. aureus to proliferate in the oral cavity is due to its arsenal of virulence factors that are coordinately expressed during different stages of infection, such as superantigens, toxins such as β-toxin, matrix-binding surface adhesins, biofilm formation, and tissue-degrading enzymes such as proteases, lipases, nucleases, and collagenases [1,31,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…are associated with suppuration and the advance of PD into a chronic state. 7 , 8 Fungi such as Candida albicans are also indicated as critical for PD persistence and progression, although its role has not yet been established. 9 Contemporary dentistry has yet to find an effective method of resolving inflammation caused by oral infections, possibly because the mechanism of the disease is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%